Comprehensive Review on Risk Assessment Methodologies for HAZMAT Transportation Between 1995-2015 - Mohd Najib, Yacob; Mimi Haryani, Hassim (Akademia Baru, 2017)
Issue related to safety, health and environmental has become major priority to be concerned of in the transportation of hazardous materials (HAZMAT) worldwide. Due to the high risk that entailed in the operation of HAZMAT transportation, many accidents in this industry have been reported which include chemicals spillage, fire and explosion. In order to quantify the degree of hazards and risks of these accidents, various assessment methods have been introduced either by the academia, the industry as well as the authority. The methods present various approaches for the assessment, ranging from a simple to highly complicated ones depending on the purpose of the assessment and the available resources and constraints. To date there is yet any study conducted to review those available methods. This paper intends to present a comprehensive review of the existing methods for hazards and risks assessment of HAZMAT transportation between years 1995-2015 which considers road, marine, railway, air and pipeline system. Based on careful screening of the abundance of methods available, 151 of them were selected – that is those specifically meant for hazards and risks assessment of HAZMAT transportation only. The methods are reviewed in terms of the types of assessment; either qualitative, quantitative or hybrid techniques, as well as their specific application in different mode of transportation. Also, statistical analysis was performed to determine the trend of past publications regarding on the type of journal, year of publication and also financial support received in the context of hazard and risk assessment of HAZMAT transportation.